Unilateral Drop Jump Kinetics and Kinematics Differentiate Patellofemoral Pain Patients from Healthy Controls - Germari Deysel; Mariaan van Aswegen; Mark Kramer (Applied Sciences)
The diagnosis of patellofemoral pain (PFP) remains imprecise due to the variable sensitivity and specificity scores of most clinical tests. More functionally relevant assessments and metrics are needed to provide better diagnostic insights. A total of 33 participants (control: n = 17 [M/F = 9/7]; PFP: n = 18 [M/F = 2/14]) volunteered for this study. The control group followed no intervention program, whereas the PFP group completed a joint-specific intervention program at a clinical practice for 8 weeks. At 0- and 8-week isometric knee extensor torques, unilateral drop jumping metrics, and anterior knee pain scale (AKPS) scores were collected and analysed. Statistically significant between-group differences were evident for the reactive strength index (RSI) (Mdiff = 0.05 m/s, p = 0.032) and ground contact time (GCT) (Mdiff = 0.28 s, p = 0.011) but not for peak force (p = 0.390), jump height (p = 0.721), impulse (p = 0.740), or peak torque (p = 0.359). While controlling for gender as a confounder, the RSI and GCT showed diagnostic utility for differentiating PFP from healthy controls (AUC = 0.83–0.87, sensitivity = 0.85–0.91, and specificity = 0.59–0.72). The AKPS score demonstrated moderate positive correlations with jump metrics (impulse: r = 0.58, 95% confidence interval (CI) [0.11, 0.83]; RSI: r = 0.50, 95% CI [0.01, 0.80]), accounting for 25–34% of performance variability. The unilateral drop jump provides useful metrics for differentiating those with PFP from their healthy counterparts. The RSI and GCT may serve as diagnostic metrics in evaluating PFP patients and can be coupled with the AKPS to track performance and rehabilitation progress in PFP patients.